Antecedents and consequences of knowledge sharing for software process improvement in the Indian software industry. Issue 2 (18th July 2020) - Chugh, Mitali; Chanderwal, Nitin; Upadhyay, Rajesh Kumar; Punia, Devendra Kumar
Abstract: The integration of knowledge sharing is significant for software process improvement (SPI). However, very few empirical studies have evaluated how and to what extent knowledge sharing affects the different aspects of SPI. Drawing upon the resource‐based view and the knowledge‐based view of software development organizations, we have explored the antecedents and consequences of knowledge sharing for SPI success. This study develops and empirically validates a model presenting how knowledge sharing impacts SPI success, how organizational factors (leadership and trust) and an individual factor (motivation) affect knowledge sharing and how the use of information technology facilitates explicitly the relation between knowledge sharing and SPI success. The empirical testing of the model has been carried out using the statistical technique of structural equation modelling (SEM) by analysing the dataset of 556 respondents collected from Indian software development organizations. The outcomes reveal that knowledge sharing enhances SPI in terms of design effectiveness, lesser fault density and improved software development competence. Also, the results show that the use of information technology moderates the relation of knowledge sharing and SPI. The conclusions also contribute to improving our knowledge about how leadership, trust and motivation drive efficient knowledge sharing on the path to SPI success. Abstract : The study empirically validates a model presenting how knowledge sharing impacts SPI success, the organizational factors (leadership and trust), and individual factor (motivation) affect knowledge sharing and how the use of information technology facilitates explicitly the relation of knowledge sharing and SPI success.